Migracije iz embalaže v živila - Golja, Viviana (Zdravstveno varstvo, 2004)
Many different substances can migrate from packaging materials to food. The paper describes the types of migration, migration testing and the respective regulations.
Keywords: embalaža; nadzor živil; živila